B0AT1 Amino Acid Transporter Complexed With SARS-CoV-2 Receptor ACE2 Forms a Heterodimer Functional Unit: In Situ Conformation Using Radiation Inactivation Analysis. Issue 4 (13th May 2021) - Stevens, Bruce R; Ellory, J Clive; Preston, Robert L
Abstract: The SARS-CoV-2 receptor, angiotensin-converting enzyme-2 (ACE2), is expressed at levels of greatest magnitude in the small intestine as compared with all other human tissues. Enterocyte ACE2 is coexpressed as the apical membrane trafficking partner obligatory for expression and activity of the B 0 AT1 sodium-dependent neutral amino acid transporter. These components are assembled as an [ACE2:B 0 AT1]2 dimer-of-heterodimers quaternary complex that putatively steers SARS-CoV-2 tropism in the gastrointestinal (GI) tract. GI clinical symptomology is reported in about half of COVID-19 patients, and can be accompanied by gut shedding of virion particles. We hypothesized that within this 4-mer structural complex, each [ACE2:B 0 AT1] heterodimer pair constitutes a physiological "functional unit." This was confirmed experimentally by employing purified lyophilized enterocyte brush border membrane vesicles exposed to increasing doses of high-energy electron radiation from a 16 MeV linear accelerator. Based on radiation target theory, the results indicated the presence of Na + -dependent neutral amino acid influx transport activity functional unit with target size molecular weight 183.7 ± 16.8 kDa in situ in intact apical membranes. Each thermodynamically stabilized [ACE2:B 0 AT1] heterodimer functional unit manifests the transport activity within the whole ∼345 kDa [ACE2:B 0 AT1]2 dimer-of-heterodimers quaternary structural complex. The results are consistent with our prior molecular docking modeling and gut–lung axis approaches to understanding COVID-19. These findings advance understanding the physiology of B 0 AT1 interaction with ACE2 in the gut, and thereby contribute to translational developments designed to treat or mitigate COVID-19 variant outbreaks and/or GI symptom persistence in long-haul postacute sequelae of SARS-CoV-2. Graphical Abstract: